Tourist entrepreneurship: from a demographic perspective - Córdova Aldás, Víctor Hugo; Castro Analuiza, Juan Carlos; Quisimalin, Mauricio (mktDESCUBRE; Vol 1 No 09 (2017): Ninth Edition - (January - June), 2017)
Tourism as the axis of development of the cities, a favorable scenario to analyze tourism ventures in Tungurahua classified in accommodation, food and beverages, travel agencies, tour operators. According to data from the Tungurahua Chamber of Tourism, there are 1,700 enterprises, 69% of which fail during the first 5 years due to factors such as financing, education and experience, analyzed from a historical and hermeneutic perspective and an informal interview. In addition, a fourth factor appears, lifestyle as of less relevance, since the marital status, the religion and the different sub groups that belong to this factor are not relevant in the emprendimientos.